LENGTH-WEIGHT RELATIONSHIP OF FISHES OF MANSAROVAR RESERVOIR BHOPAL - CHAKRAWARTI, ARUNA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2006)
The Present paper embodies the study of furcal length and body weight relationship in economically important and abundantly found fishes from lentic water body i.e. Mansarovar reservoir, Bhopal. The high values of coefficient of correlation "r" (between 0.9401 to 0.9954) showed a strong positive correlation between length and weight in all cases, revealed that applicability of equation derived is high. The results obtained revealed that Clarias batrachus (n = 3.1151) were most conductive for Mansarovar reservoir, because only this fish should the 'n' value more than 3. The value of Labeo fimbriatus (n = 2.6157 and Labeo bata (n = 2.2500) showed slight decreases in growth constant while rest of the fishes Notopterus notopterus (n = 1.4177), Mystus seenghala (n = 1.9197), Labeo calbasu (n = 1.3405) and Puntius sarana (n = 1.1214) had quite low values. The factors responsible for decrease in growth constant are dietary, topography, taxonomic and water quality of the lakes.